Wayne's world 2 [videorecording (DVD)] - Myers, Mike, 1963-; Carvey, Dana; Carrere, Tia; Walken, Christopher, 1943-; Basinger, Kim, 1953- (Widescreen DVD collection., 2001)
Wayne and Garth are back, this time trying to organize a rock festival. Meanwhile, Cassandra's manager is busy trying to woo her. Wayne must rush from the concert and try and stop Cassandra's wedding. The concert features Aerosmith.